Approach to a feasibility analysis method for the deployment of software systems for SMEs - Moreno, Leandro (2024)
The deployment of software systems is a vital process in the software development life cycle since after a successful deployment, the software system is finally operational for the client to economically benefit from its use. During deployment, there may be some drawbacks which adversely affect organizations, usually causing loss of economic resources. This paper presents a method for analyzing the deployment feasibility of software systems to help small and medium enterprises (SMEs) to identify any deployment elements requiring adjustments or revisions in order to achieve a successful outcome, integrating an organizational vision to the technical analysis. Furthermore, the research steps followed are described, from the state of the art which justifies the need for the method to the initial validation in two software development SMEs from Argentina.